TYPES OF MORPHEMES AND THEIR CLASSIFICATION. MORPEMIC ANALYSES. STRUCTURAL ANALYSIS. ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article examines the fascinating field of Morphemes and its types, classifications. Morphemic analysis.Structural analysis and how they are essential and often challenging aspect of learning English.Morphemes are the smallest units of language that carry meaning. They can be classified into different types based on their function and meaning within a word. Understanding the different types of morphemes is crucial for gaining insight into the structure of words and how they contribute to the overall meaning of a language.In English grammar and morphology, a morpheme is a meaningful linguistic unit consisting of a word such as dog, or a word element, such as the -s at the end of dogs, that can't be divided into smaller meaningful parts.